2011
DOI: 10.1007/s13213-011-0341-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening of glucosinolate-degrading strains and its application in improving the quality of rapeseed meal

Abstract: Two myrosinase-producing fungi, Lichtheimia sp. JN3C and Aspergillus terreus, were newly isolated from decayed rapeseed meal samples obtained in Anhui Province, China. After preliminary screening, re-screening and combination of two screened strains with a yeast, an optimal composite strain to ferment rapeseed meal was obtained. Results demonstrated that the glucosinolate content of products with two molds fermentation was overall lower than that with single strain fermentation. Fermentation with composite str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 31 publications
(27 reference statements)
0
15
0
1
Order By: Relevance
“…Microbial fermentation has been widely used for the detoxification of rapeseed meal. It provides an effective approach to degrade glucosinolates without loss of proteins (Wang et al ., ). Wang et al .…”
Section: Resultsmentioning
confidence: 97%
“…Microbial fermentation has been widely used for the detoxification of rapeseed meal. It provides an effective approach to degrade glucosinolates without loss of proteins (Wang et al ., ). Wang et al .…”
Section: Resultsmentioning
confidence: 97%
“…The results showed that glucosinolates, phytic acid and crude fiber were reduced by 43.1%, 42.4% and 25.5%, respectively, after fermentation [6]. Wang et al (2012) used composite strains to eliminate the anti-nutritional substances in rapeseed meal, the phytic acid and crude fiber were reduced by 28.3% and 66.2%, respectively [21]. In the present study, the reduction of glucosinolates, phytate and NDF by fermentation might due to the production of relevant enzyme by A. niger which cause the breakdown of anti-nutritional substrates.…”
Section: Discussionmentioning
confidence: 99%
“…; Vig & Walia ; Wang et al . ). The filamentous fungus Aspergillus niger , generally recognized as a safe (GRAS) microorganism, is well‐known as a producer of extracellular enzymes.…”
Section: Introductionmentioning
confidence: 97%